METHODS TO ENHANCE STUDENTS’ CREATIVE ACTIVITY THROUGH THE INTEGRATION OF NATIONAL MOTIFS IN VISUAL ARTS LESSONS - Usmonova Ruxshona Feruz qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores methods for enhancing schoolchildren’s creative activity through the integration of national motifs in visual arts lessons. The study focuses on pedagogical strategies that combine cultural content, artistic techniques, and interactive activities to stimulate creativity, aesthetic perception, and cultural awareness. By incorporating national motifs such as traditional patterns, symbols, and folk art elements into visual arts education, teachers can foster students’ imaginative thinking, critical analysis, and expressive skills. Practical recommendations for lesson planning, implementation, and evaluation are provided to optimize creative engagement and promote cultural appreciation.